DFT studies of the adsorption and interaction of two methanol molecules on a MgO edge - Rodríguez, Angel Horacio (2006)
The adsorption of two methanol molecules on an edge along the [001] direction of MgO was studied. The calculations were carried out within the DFT formalism employing an embedded cluster model approach. From the four possible geometrical configurations of dimers, one of them shows the dissociation of a methanol molecule. In order to attain a deeper understanding of substrate influence on this process, the adsorption energy was considered as a contribution mainly due to the direct interaction with the substrate and, separately, another one coming from the methanol-methanol interactions. The results indicate that the first adsorbed methanol molecule acts like a new defect at the surface and it turns more reactive the MgO edge site. © 2006 Elsevier B.V. All rights reserved.